Cytosolic HMGB1 Expression in Human Renal Clear Cell Cancer Indicates Higher Pathological T Classifications and Tumor Grades - Takeuchi, Takumi; Sakazume, Koichi; Tonooka, Akiko; Zaitsu, Masayoshi; Takeshima, Yuta; Mikami, Koji; Uekusa, Toshimasa (Urology Journal, 2013)
Purpose: High mobility group box (HMGB) proteins are nuclear nonhistone chromosomal proteins that bend DNA, bind preferentially to distorted DNA structures, and promote the assembly of site-specific DNA binding proteins. Recent reports indicate that HMGB1 functions as a proinflammatory cytokine. Here, we studied expressions of HMGB1 and HMGB2 in human renal cancer. Material and Methods: Immunohistological expressions of HMGB1 and HMGB2 were assessed in 39 surgically resected human renal cancer specimens. Results: HMGB1 was expressed in the nucleus in 37 out of 39 (94.9%) renal clear cell cancers, while its expression in the cytosol was noted in 19 cases (48.7%). Cytosolic HMGB1 is expressed more frequently in cancers beyond the pT1b classification than in those at the pT1a classification. Higher tumor grades (≥ G2) were also significantly linked with the cytosolic expression of HMGB1. HMGB2 was expressed in the nucleus in 35 of 39 (89.7%) renal clear cell cancers, while its expression in the cytosol was observed in only 7 case (17.9%). Linkage between cytosolic expression of HMGB2 and T classifications was weakly observed, while that between nuclear expression and T classifications was not. Conclusion: HMGB1 expressed in the cytoplasm may be an effective marker indicating higher T classifications and tumor grades.